Safety Criteria and Dependability Management Practices: A Case Study with I&C Systems of Prototype Fast Breeder Reactor. (1st February 2018) - Sravanthi, Srikantam; Dheenadhayalan, R.; Madhusoodanan, K.; Devan, K.
Abstract: Dependability management practices in nuclear power plants in India are conventionally governed by a set of rules known as "safety criteria." Probabilistic assessments of safety systems are used in a modern plant to complement such rules. In this technical note, various design provisions provided in the instrumentation and control (I&C) of prototype fast breeder reactor (PFBR) (a reactor under commission in India) are detailed. As a precursor, the relationship between safety criteria and the average probability of failure on demand (PFDAvg ) of safety systems is established. Subsequently, various design provisions provided in the I&C of PFBR to reduce PFDAvg are discussed. Such a review, with a dependability viewpoint, has resulted in identifying areas for further design improvement in future reactors. Research work carried out in areas of relays toward reducing PFDAvg of safety systems is highlighted.